A final reckoning : a Hannover family's life and death in the Shoah - Herskovits-Gutmann, Ruth, 1928- (Judaic studies series (Unnumbered), 2013)
"A work of both childhood memory and adult reflection undergirded with scholarly research, A Final Reckoning resonates with emotional intensity and insight. Ruth Gutmann's memoir, first published in Germany in 2002, recounts her life not only as a concentration camp inmate and survivor, but also as a sister and daughter. Ruth; her twin sister, Eva; stepmother, Mania; and father, Samuel Herskovits, were interned in both Thereisenstadt and Auschwitz-Birkenau between June 1943 and March 1944, where all but Gutmann and her sister perished. Ruth and Eva spent the remainder of the war in numerous other camps. Gutmann's memoir is compelling in several respects. It spans her birth and early life in Hannover, Germany; her escape to Holland on a kindertransport; her forced return to Hannover; her deportation to the concentration camps (where Ruth and Eva attracted the attention of Josef Mengele, though they were ultimately spared from his murderous studies of twin siblings); and her life postliberation. Particularly striking is Gutmann's portrait of her father, Samuel, a leader in the Jewish community of Hannover who was forced under extreme pressure to communicate and, in some cases, cooperate with Nazi officials. Gutmann uses her own memories as well as years of reflection and academic study to reevaluate his role in their community. A Final Reckoning provides not only insights into Gutmann's own experience as a child in the midst of the atrocities of the Holocaust, but also a window into the lives of those, like her father, who were forced to carry on and comply with the regime that would ultimately bring about their demise"--